How to design an area-based prioritization of biogas production from organic municipal solid waste? Evidence from Thailand - Chaianong, Aksornchan; Pharino, Chanathip (Waste Management, 2022)
To properly manage municipal solid waste (MSW) and meet the country's biogas target, it is necessary for the government to prioritize their support to areas/provinces that have high resource potential. Therefore, this work designed a holistic approach for nationwide area-based organic MSW to biogas potential estimation. The total biogas power potential was ranged from 999 MW in 2021 to 1,652 MW in 2037. Moreover, priority setting on area-based biogas implementation was proposed, based on its resource potential to efficiently promote such technology. To achieve current biogas target of the country, the study identified 28% of national area coverage as priorities for actual execution, which could offset averagely 3% per year. To support design and planning purposes, an area with around 45,000 capita is recommended for developing 1 MW of MSW to biogas power plant using anaerobic digestion technology. The methodology development from this research revealed the link between resource potential and area-based prioritization framework that could be adopted in any growing economies to couple waste management with renewable energy production.
Created from Fastlane, Scopus look-up
Keywords: Anaerobic digestion; Area-based biogas; Organic MSW; Prioritization; Thailand; Waste-to-energy